Incretins or Anti-Incretins? A New Model for the “Entero-Pancreatic Axis” - Kamvissi, V.; Salerno, A.; Bornstein, S. R.; Mingrone, G.; Rubino, F. (Hormone and Metabolic Research, 2015)
The role of incretins in glucose homeostasis is well known. Yet, in recent years, the sustained weight loss and rapid glycemic control following bariatric surgery has challenged our understanding of the intestinal-pancreatic interaction. This in turn led to the introduction of metabolic surgery, an innovative medical discipline in which a surgical manipulation of the gastrointestinal tract (e. g., through a Roux-en-Y gastric bypass, RYGB, or Bilio-Pancreatic-Diversion, BPD) yields a sustained remission of diabetes mellitus. The pathophysiological background of this metabolic effect is, amongst other things, based on the anti-incretin theory. This theory postulates that in addition to the well-known incretin effect, nutrient passage through the GI-tract could also activate negative feedback mechanisms (anti-incretins) to balance the effects of incretins and other postprandial glucose-lowering mechanisms (i. e., suppression of ghrelin, glucagon, and hepatic glucose production via activation of nutrient sensing). This in turn prevents postprandial hyperinsulinemic hypoglycemia. The bypass of the duodenum, the entire jejunum and the first portion of the ileum by BPD induce normalization of peripheral insulin sensitivity, while the bypass of a shorter intestinal tract by RYGB mainly improves the hepatic insulin sensitivity. In addition, RYGB greatly increases insulin secretion. Therefore, metabolic surgery highlights the important role of the small intestine in glucose homeostasis, while until few years ago, it was only the pancreas and the liver that were thought to represent the regulatory organs for glucose disposal.
Keywords: incretins; metabolic surgery; anti-incretin theory; pancreatic islets